2007
DOI: 10.1002/rcm.3209
|View full text |Cite
|
Sign up to set email alerts
|

Stable 2H isotope analysis of modern‐day human hair and nails can aid forensic human identification

Abstract: Continuous-flow isotope ratio mass spectrometry (CF-IRMS) was used to compare (2)H isotopic composition at natural abundance level of human scalp hair and fingernail samples collected from subjects worldwide with interpolated delta(2)H precipitation values at corresponding locations. The results showed a strong correlation between delta(2)H values of meteoric water and hair (r(2) = 0.86), while the corresponding correlation for nails was not as strong (r(2) = 0.6). Offsets of -180 per thousand and -127 per tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 18 publications
6
61
0
Order By: Relevance
“…Since both finger and toenail tissue of each individual had almost the same δ 2 H value over the whole growth time, δ 2 H values along the hair strand changed distinctly with a remarkable enrichment in younger hair segments. An enrichment of 2 H values in human hair compared to nail tissue by a mean value of 6‰ can also be seen in the results of Fraser and Meier-Augenstein [9]. Contrary to our study, the authors took hair samples directly from the scalp, which were compared with nail samples clipped off at the distal edge of the nail.…”
Section: Hydrogensupporting
confidence: 53%
See 1 more Smart Citation
“…Since both finger and toenail tissue of each individual had almost the same δ 2 H value over the whole growth time, δ 2 H values along the hair strand changed distinctly with a remarkable enrichment in younger hair segments. An enrichment of 2 H values in human hair compared to nail tissue by a mean value of 6‰ can also be seen in the results of Fraser and Meier-Augenstein [9]. Contrary to our study, the authors took hair samples directly from the scalp, which were compared with nail samples clipped off at the distal edge of the nail.…”
Section: Hydrogensupporting
confidence: 53%
“…Although there is a tendency for a 'global supermarket' diet, isotope signatures in human tissues hold dietary information directly related to both food sources and dietary practices in a region [5][6][7]. Several studies have demonstrated the potential of multi-element stable isotope analysis as a tool for determining the place of origin of living humans, unidentified humans and the identification of disaster victims [8][9][10][11][12]. Description of regional differences is possible using stable isotope ratios of bio-(H, C, N, O and S) and geo-elements (Sr and Pb).…”
Section: Introductionmentioning
confidence: 99%
“…H and O isotope ratio analysis has been applied to questions of origin or migration in nonhuman keratin tissues such as bird feathers (Hobson et al, 1999a(Hobson et al, , 2004 and butterfly wing keratin (Hobson et al, 1999b). However, data from human hair (Sharp et al, 2003;O'Brien and Wooller, 2007;Ehleringer et al, 2008) and nail keratin (Fraser et al, 2006;Fraser and Meier-Augenstein, 2007) have recently been published.…”
Section: Stable Isotope Systematicsmentioning
confidence: 99%
“…Abundances of these isotopes, therefore, provide an indication of the dietary lifestyle and geographical origin of an individual. Following on from some of the fundamental studies of Ehleringer et al [27] investigating the links between stable isotope signatures in hair of US residents and geographic provenance, Fraser et al [26,28] developed isotope profiling methods for hair and nails.They conducted studies yielding information about the intra-and inter-variability of individuals within a geographical area [26] and have demonstrated that information regarding recent geographical whereabouts can be obtained from 2H isotope profiling of hair and nail samples. [28] Meier-Augenstein and Fraser [29] reported the first use of isotope analysis in aiding the identification of an unknown victim.…”
Section: Irms Of Explosivesmentioning
confidence: 99%
“…They examined hair and nail samples from a dismembered body. Using data obtained from their previous longitudinal study, [27] as well as data from the Global Network for Isotopes in Precipitation, they were able to provide sufficient information about the likely geographical origin of the victim and approximate time period of entry into the country. This allowed investigators justification for DNA analysis that resulted in identification of the victim.…”
Section: Irms Of Explosivesmentioning
confidence: 99%